Accuracy of the Modified Finnish Diabetes Risk Score (Modified FINDRISC) for detecting metabolic syndrome: Findings from the Indonesian national health survey - Indriastuti Cahyaningsih; M. Rifqi Rokhman; Sudikno; Maarten J. Postma; Jurjen van der Schans (PLoS ONE, 2025)
Background This study evaluated the diagnostic accuracy of the Modified Finnish Diabetes Risk Score (Modified FINDRISC) for detecting individuals with metabolic syndrome in Indonesia. Methods A dataset from the 2018 Indonesian National Basic Health Survey was analysed, and cases of metabolic syndrome were identified in accordance with both National Cholesterol Education Program Adult Treatment Panel III (NCEP-ATP III) and International Diabetes Federation (IDF) guidelines. Diagnostic accuracy of the Modified FINDRISC tool was evaluated using the Area Under the Receiver Operating Characteristic (AUC) curve, while optimal cut-off scores were determined by Youden’s Index. Results From 25,432 participants, the mean and standard deviation of the Modified FINDRISC score was 5.7 (SD 4.1). The prevalence of metabolic syndrome was 32.1% and 24.8% based on NCEP-ATP III and IDF criteria, respectively. Based on NCEP-ATP III criteria alone, the AUC of the Modified FINDRISC was 80.9% (80.3%-81.5%) with 74.0% sensitivity and 75.5% specificity. Similarly, based on IDF criteria, AUC was 88.9% (88.5%-89.3%) with 89.8% sensitivity and 75.8% specificity. The optimal cut-off score was 6 for both criteria, with 41.2% of the total participants above the cut-off who would require further confirmation tests. Conclusion Metabolic syndrome is prevalent in Indonesia, and the Modified FINDRISC tool offers good diagnostic accuracy for detecting such cases. Utilising Modified FINDRISC as a first-instance screening modality will reduce the number of people requiring further confirmation tests. Modified FINDRISC has the potential for use in daily clinical practice, and the cost-effectiveness of Modified FINDRISC should be further evaluated.